Advanced Active Power Line Conditioners For Power Quality Improvement - -, Moleykutty George (2008)
Power quality broadly refers to the delivery of sufficiently high grade of electric service to the distribution system customers. Ideally, utility must maintain purely sinusoidal voltage at rated magnitude and frequency at the distribution system consumer terminals. To meet this objective, it is a recommended practice for power system engineers to follow international/national standards. One may note that poor power quality will eventually lead to high financial losses.